Emotional Abuse History and Migraine Among Young Adults: A Retrospective Cross‐Sectional Analysis of the Add Health Dataset. Issue 1 (5th December 2016) - Tietjen, Gretchen E.; Karmakar, Monita; Amialchuk, Aliaksandr A.
Abstract : Objectives: To define and examine the relationship between self‐reported childhood abuse and migraine among young adults. Background: Headache and migraine have been linked to childhood abuse in numerous studies, but there is incomplete characterization of headache types, and limited assessment of abuse types and frequency. Only one population‐based study has examined the relationship between emotional abuse and migraine. None have investigated the temporal relationship between onset of abuse and of migraine. Methods: We analyzed data from 14, 356 adults aged 24–32 years in Wave 4, which is a cross‐sectional subset of the longitudinal Add Health study. Participants were queried regarding abuse (emotional, physical and sexual) during childhood, diagnosis of migraine, depression and anxiety by healthcare providers, and symptoms of current depression. We used logistic regression to estimate the association between childhood abuse and migraine, controlling for socio‐demographic factors, current depression, and lifetime diagnosis of anxiety and depression. Results: About 14% (n = 2040) of respondents reported migraine. Participants with migraine (vs no migraine) reported significantly higher rates of childhood abuse overall (60.6% vs 48.9%), including emotional (57.8% vs 45.4%), sexual (8.4% vs 4.6%) and physical (22.4% vs 17.9%) abuse. Emotional abuse had a stronger association with migraine (odds ratio [OR] 1.62; 95% confidence interval [CI] 1.43–1.85) when compared with physical (OR 1.06; 95% CI 0.89–1.68) and sexual abuse (OR 1.06; 95% CI 0.93–1.68), adjusting for socio‐demographic factors. The emotional abuse‐migraine association remained even when controlling for lifetime diagnosis of depression and anxiety (OR 1.37; 95% CI 1.19–1.57) and for current depression (OR 1.47; 95% CI 1.30–1.67). The odds of migraine increased with increasing number of abuse types reported. There was a U‐shaped distribution of odds of migraine associated with frequency of occurrences of emotional abuse, peaking at one time (OR 1.65; 95% CI 1.34–2.03) and ≥ six times (OR 1.77; 95% CI 1.49–2.10). Conclusions: Emotional abuse during childhood contributed more than physical or sexual abuse to the development of migraine. There is a dose–response relationship with increasing number of abuse types associated with rising odds of migraine. In addition, the relationship between the frequency of emotional abuse and the odds of migraine follows a U‐shape pattern.